THE ASSOCIATION OF BREASTFEEDING WITH POSTPARTUM WEIGHT LOSS - Ana Maria Alexandra Stănescu; Constantin Ştefani; Ioana Veronica Grăjdeanu; Daniela Oana Toader; Alexandra Totan; Daniela Miricescu; Bogdan Şerban; Camelia Cristina Diaconu (Romanian Medical Journal, 2019)
Breastfeeding has many benefits for both baby and mother and socio-economic point of view. From the perspective of the benefits to the mother, an advantage is the faster weight loss compared to the non-breastfeeding mothers. We will discuss the extent to which weight loss in breastfeeding mothers is relevant, based on the results of the latest research in the field.